THE EFFECT OF APPLYING ENGLISH COMIC MEDIA ON THE STUDENTS’ READING SKILLS AT THE SEVENTH GRADE OF SMPN 2 LEMBAH MELINTANG - Rahma, Asriza (Faculty of Tarbiyah nad Teacher Training, 2023)
This research aimed to find out wheter there was a significant effect of applied English comic media on the students’ reading skills which was observed and analyzed from students in the seventh grade of SMPN 2 Lembah Melintang. The research methodology was quantitative research by using experimental research design. The population of this research was the seventh grade students of SMPN 2 Lembah Melintang. The sample of this research was two classes, there were Experimental class (VII2) as many as 30 students and control class (VII3) as many as 30 students. The researcher applied English comic media in the experimental class and taught by whiteboard media in the control class. The researcher used reading test after the treatment, namely post-test to collecting the data. After analyzed the data used statistic calculation and microsoft office excel calculation, the result of this research showed that the value of tobserved(2,564) was higher than ttable (2,002) at the level significant 0,05 and deegre of freedom was 58. So, it can be concluded that applied English comic media has significant effect in the students’ reading ability and the alternative hypothesis (Ha) was accepted.